Surgical Site Infections in patients undergoing major oncological surgery during the COVID‐19 paNdemic (SCION): A propensity‐matched analysis. Issue 3 (3rd November 2021) - Pantvaidya, Gouri; Joshi, Shalaka; Nayak, Prakash; Kannan, Sadhana; DeSouza, Ashwin; Poddar, Pabashi; Prakash, Gagan; Vijaykumaran, Preeti; Nair, Deepa; Vaish, Richa; Patkar, Shraddha; Niyogi, Devayani; et al.
Abstract: Background and Objectives: There are reports of outcomes of elective major cancer surgery during the COVID‐19 pandemic. We evaluated if reinforcement of hand hygiene, universal masking, and distancing as a part of pandemic precautions led to a decrease in the incidence of surgical site infections (SSIs) in major oncologic resections. Methods: Propensity score matching using the nearest neighbor algorithm was performed on 3123 patients over seven covariates (age, comorbidities, surgery duration, prior treatment, disease stage, reconstruction, and surgical wound type) yielding 2614 matched (pre‐COVID 1612 and COVID 1002) patients. Conditional logistic regression was used to identify if SSI incidence was lower amongst patients operated during the pandemic. Results: There was a 4.2% ( p  = 0.006) decrease in SSI in patients operated during the pandemic. On multivariate regression, surgery during the COVID‐19 period (odds ratio [OR] = 0.77; 95% confidence interval [CI] = 0.61–0.98; p  = 0.03), prior chemoradiation (OR = 2.46; CI = 1.45–4.17; p  < 0.001), duration of surgery >4 h (OR = 2.17; 95%CI = 1.55–3.05; p  < 0.001) and clean contaminated wounds (OR = 2.50; 95% CI = 1.09–2.18; p  = 0.012) were significantly associated with SSI. Conclusion: Increased compliance with hand hygiene, near‐universal mask usage, and social distancing during the COVID‐19 pandemic possibly led to a 23% decreased odds of SSI in major oncologic resections. Extending these low‐cost interventions in the post‐pandemic era can decrease morbidity associated with SSI in cancer surgery.